Formulasi Sediaan Losio Dari Esktrak Kulit Buah Delima (Punica Granatum L.) Sebagai Tabir Surya - Iyan Iyan Sopyan; Rosa Apriana Apriana; Dolih dolih Gozali (Farmaka, 2016)
Pomegranate peel has a natural compound that is used as a sunscreen. A lotion was one of the simple sunscreen products. The purpose of this research was to make a lotion from pomegranate peel extract (Punica granatum L.) which was good, stable, appeal and safe to be used. Stages on research were extract preparations, measurment of the Sun Protector Factor (SPF) value of pomegranate peel extract using Petro method, selecting base of lotion, physical observations test that including measurement of pH, viscosity, centrifugation test, freeze-thaw cycle during 28 days, the skin irritation test, the effectiveness of sunscreen and qualitative test by Thin Layer Chromatography. Concentrations of pomegranate peel extract (Punica granatum L.) in formulation of sunscreen lotions were 0,055%, and 0,066% w/w.The results showed that the sunscreen lotions had good physical quality and safe to be used. A lotion that containing a pomegranate peel extract 0,055% give effectivity as a sunscreen that is showed  in SPF is 16,63 and 44,05.